Thriving in a World of Giants: Craft Breweries’ Workings in a Major Tourism Destination - Carrillo, Brendali (2024)
Major tourism destinations depending on iconic resources to draw tourists are seeking to diversify their offerings. Building upon neolocalism, craft-beverage tourism has emerged as a diversification strategy. Such a strategy requires establishing a vibrant craft-beer industry that, according to the resource partitioning theory (RPT) requires applying four mechanisms (location, anti-mass production sentiment, customization, and conspicuous status). Since it is unknown how the RPT unfolds in tourism destinations, we interviewed 21 producers in Cusco (Peru), a major destination with an emerging craft-brewery industry, to identify the strategies they are utilizing to position their products when juxtaposed with tourism and neolocalism. We identified 17 actions that local craft-brewers apply and a strong tourism-neolocalism intersection, which altogether enriches the RPT. Findings suggest that craft-brewers build upon local places and culture to differentiate from, rather than fight against, their competitors. Findings can also guide agencies seeking to diversify the tourism offerings through craft-beverage tourism.